Resale Royalty Right (RRR) in Malaysia: a preliminary needs assessment of policy readiness among visual artists - Mohamad Kahar, Nur Suraya; Masrek, Mohamad Noorman; Ramli, Ishak; Merman, Hairulnisak (Universiti Teknologi MARA, Perak, 2025)
The Resale Royalty Right (RRR) is a legal mechanism that entitles visual artists to a fixed percentage of proceeds whenever their artworks are resold in the secondary market. As of 2023, over 106 countries have adopted some form of RRR legislation, including the European Union, Australia, the United Kingdom, and New Zealand. These policies aim to ensure that artists benefit from the long-term value their works generate, an objective that remains unmet in Malaysia’s current legal framework. Despite the expansion of Malaysia’s creative economy and the rise of domestic art auctions, the country’s copyright law does not include resale royalty provisions for visual artists. This exclusion perpetuates economic inequity and highlights a broader policy gap in aligning artist rights with evolving international standards. Moreover, preliminary observations suggest that awareness of RRR among Malaysian artists is low, and institutional trust in enforcement bodies is a limited factor that is likely to affect future implementation. This article presents a preliminary needs assessment of Malaysia’s readiness to adopt RRR by integrating four theoretical lenses: Situation Awareness Theory, Social Capital Theory, Theory of Practice, and Institutional Theory. It identifies cognitive, experiential, social, and institutional variables that shape policy readiness and proposes a framework for future empirical research and policy development. By diagnosing informational gaps, trust deficits, and engagement barriers, this study provides a foundation for equitable policy design and contributes to national goals under the Creative Industry Policy and Sustainable Development Goals (SDG 8 and SDG 10).